Metagenomic Analysis of the Sputum Microbial Community in Pneumonia Patients Using Targeted NGS Sequencing - Strochkov, V.M.; Orkara, Sh.D.; Beloussov, V.Yu.; Solomadin, M.V.; Yegorov, S.V.; Lavrinenko, A.V.; Sandybayev, N.T. (Eurasian Journal of Applied Biotechnology, 2025)
This study presents the results of analyzing the sputum microbiome of 46 patients diagnosed with pneumonia using targeted NGS sequencing of the 16S rRNA gene. As a result of the study, 114 species of bacteria belonging to 47 genera and 29 families were identified. Based on the obtained data, potential pathogens associated with the development of pneumonia were identified, and a quantitative analysis of their prevalence among patients was conducted. At the species level, Streptococcus pneumoniae was detected in 26 samples (56.5%). Acinetobacter baumannii was found in 10 samples (21.7%). Klebsiella pneumoniae was detected in 9 samples (19.5%), and Pseudomonas aeruginosa was found in 17.4% of samples. Other species that may be involved in the development of pneumonia included Escherichia coli, Haemophilus influenzae, and Staphylococcus aureus in 15.2%, 10.87%, and 8.7% of samples, respectively. Additionally, Neisseria meningitidis was detected in 5 samples (10.8%), and Stenotrophomonas maltophilia was found in two samples. The obtained results can contribute to a deeper understanding of microbiome communities associated with pneumonia and enrich knowledge about the microbiome of the upper respiratory tract. These data may be useful for developing new strategies for the diagnosis and treatment of pneumonia, as well as for optimizing preventive measures.